Association between Authoritative Parenting Style and Caregiver Stimulation among Preschool-Aged Children in Indonesia - Yuri Nurdiantami; Hilda Meriyandah Agil; Smarika Shrestha; Xiang Li; Tokie Anme (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Background: Nurturing care within the home environment is fundamental to early childhood development. Parenting style may influence caregiver-provided stimulation, a key component of nurturing care. This study aimed to examine the association between authoritative parenting style and caregiver stimulation as forms of nurturing care among Indonesian preschool-age children. Methods: A cross-sectional study was conducted in 2023 among 382 parents of children aged 3 to 6 years enrolled in kindergartens in Jakarta. Data were collected using self-administered questionnaires, including the Parenting Styles and Dimensions Questionnaire (PSDQ) and the Index of Child Care Environment (ICCE). Multivariable logistic regression analysis was performed to assess the association between authoritative parenting style and adequate caregiver stimulation, adjusting for parent working status, parent age, parent gender, and number of children in the household. Results: The mean age of the children was 60.4 months (SD = 13.87), and 50.5% were boys. The regression analysis showed that an authoritative parenting style was significantly associated with higher odds of sufficient caregiver stimulation (adjusted OR = 2.61, 95% CI: 1.40–4.88; p < 0.005). Conclusions: Authoritative parenting style was positively associated with caregiver stimulation among preschool-aged children in Jakarta. Parents may consider adopting parenting approaches that support optimal early childhood development.